PROPOSED MARKETING STRATEGY FOR CREVOLENE PRODUCT FROM EVOLENE COMPANY TO INCREASE SALES - Revzand Hasibuan, Yuliando
The Indonesian market for dietary supplements, including products like Crevolene, has seen significant growth due to the increasing focus on health and wellness. With a rise in fitness activities and a health-conscious population, there is a target market for such supplements. From the interview with the CEO of Evolene, it revealed a notable fluctuation in Crevolene sales since November 2022, raising concerns about revenue stability and sustainable growth. Understanding the contributing factors, such as changing consumer preferences, market dynamics, and pricing fluctuations, is crucial to develop effective marketing strategies. Preliminary findings suggest that Crevolene is gaining recognition among individuals who engage in regular workout routines, indicating a potential target market. By focusing marketing efforts on this segment and analyzing purchase intentions, Evolene can tailor strategies to increase sales and align with customer preferences. Further research is needed to refine market segmentation and develop precise targeting strategies. The purposes of this study are to identify the factors that influence Crevolene product from Evolene company sales and to increase sales of Crevolene product of Evolene Company. This study uses a quantitative research method with descriptive statistics. The sample for this research consists of 207 respondents taken by using non-probability sampling method. The questionnaire will employ a Likert scale with five levels, representing an interval scale. Questionnaire will be distributed online. The research tool used in this research is questionnaire. The data analysis methods are divided into two namely internal analysis (4P marketing mix and STP) and external analysis (Porter’s strength analysis, competitor analysis, consumer analysis and PESTEL analysis). Then, data are analyzed using SWOT and TOWS analysis. Based on the research results showed that companies must do cost efficiency so it could easily attract a potential customer or existing customer to purchase / repurchase the Evolene. Packaging that offers convenience and portability can be appealing to consumers. Features such as resealable bags, single-serve packets, or compact containers make it easier for consumers to carry and use the supplements during their fitness routines or on the go. Packaging that enhances convenience and usability can positively influence purchase intention. For the strategies that we could implement in Evolene are leverage strong brand reputation to expand internationally, improve cost competitiveness to address price sensitivity, strengthen competitive position through product differentiation.